Spatiotemporal analysis of soil erosion under land use and rainfall variability using RUSLE and RS-GIS techniques: A case study of Irga River Catchment, Jharkhand, India - YADAV, SHANKAR; SAHU, RAM KUMAR (Journal of Soil and Water Conservation, 2026)
Soil Erosion is a serious environmental concern, which severity can assess using the Revised Universal Soil Loss Equation (RUSLE) alongside remote sensing and geographic information system (RSGIS) techniques. This study investigates the spatiotemporal changes in soil erosion potential between 2007 and 2017, due to the impact of rainfall patterns and land use/land cover (LULC) changes in the Irga River catchment, which lies in the Chhota Nagpur Plateau and is susceptible to severe soil erosion due to anthropogenic pressures. The study incorporates 20 years of average annual rainfall data (1998-2017) from the Tropical Rainfall Measuring Mission (TRMM) to calculate the Rainfall-Runoff Erosivity factor (R) and utilises FAO soil data for soil erodibility factor (K) determination. Digital elevation models (DEM) are utilized to derive the Topographic factor (LS), and LULC maps for both years are used to create Crop Management (C) and Soil Conservation Practice (P) factor maps. Soil erosion estimates for 2017 averaged 0.2814 t/ha/year, with rates ranging from 0 to 36.1185 t/ha/year, while for 2007, the average was 0.3057 t/ha/year, with rates from 0 to 44.2149 t/ha/year. The study reveals that the catchment experiences very mild and slight erosion, with most wasteland in the northwest and north. Over a decade (2007-2017), the average erosion rate decreased by 8.6%, highlighting the impact of LULC changes and rainfall patterns on soil erosion.